Oil-water emulsion separation on surface-modified capillary ultrafiltration membranes - A. S. Ilyinykh; E. V. Migalatiy; A. V. Korneev (Vestnik MGSU)
Introduction. The accumulation of oily wastewater in the environment is becoming an increasing threat to the ecosystem and human health. The modification of ultrafiltration PVDF membrane was investigated in order to create a hydrophilic layer on its surface, to improve performance and increase antifouling properties in the purification of oil-water emulsions.Materials and methods. PVDF hollow-fibre capillary membranes with 0.1 μm diameter pores were used. The membranes were subjected to two-step modification, which included treatment with tannic acid and subsequent oxidation with potassium permanganate in various buffer solutions. Motor oil, kerosene, distilled water and sodium dodecyl sulfate were used to create model water-in-oil emulsions. All oil-water emulsion separation experiments were performed while maintaining a constant filtration pressure of 1 bar on a prepared filter cell, in dead-end mode. The prepared model solutions were made with sodium dodecyl sulfate and contained the pollutant motor oil or kerosene. The filtrate after the membrane was sampled to determine the permeability and separation efficiency of the solutions. Surface modification had a positive effect on the retention efficiency of petroleum products. In the case of motor oil emulsion separation, the efficiency reached 99 %, and the content of oil products in all filtrate samples was below 0.4 mg/l. In the case of separation of kerosene emulsion there was observed a slight decrease in the efficiency of purification up to 95 %, the content of oil products was below 1.15 mg/l.Results. The results obtained showed a significant increase in throughput and separation efficiency. The specific membrane performance increased up to 143 % for motor oil separation and up to 67 % for kerosene separation.Conclusions. The modified membranes showed high petroleum product removal efficiency, up to 99 % for motor oil and up to 98 % for kerosene, also had high flux recovery rate (FRR) up to 91 %. The results obtained may be promising for scaling up.